2015
DOI: 10.1097/igc.0000000000000551
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes After Extensive (Ultraradical) Surgery for Ovarian Cancer: Results From a Prospective Longitudinal Feasibility Study

Abstract: This study provides useful insight into the impact of extensive surgery on patients. Further multicenter studies are needed to evaluate the impact of extensive surgery on patient's QoL and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…Nevertheless, many of the patients who underwent surgery at both centers participated in the international, multicenter, prospective SOCQER 2 study of “patient-reported outcomes after surgery in advanced ovarian cancer”. The preliminary analysis in this study showed no association between surgical complexity and global health status at 12 months, whereas extensive surgery did not seem to cause a decrease in patient quality of life compared with preoperative scores 9,24. The currently ongoing international Trial of Radical Upfront Surgical Therapy in advanced ovarian cancer (AGO-OVAR-OP.7/NCT02828618) is set to address more of these important quality-of-life questions25 and also impact of timing of surgery on overall outcome.…”
Section: Discussionmentioning
confidence: 49%
“…Nevertheless, many of the patients who underwent surgery at both centers participated in the international, multicenter, prospective SOCQER 2 study of “patient-reported outcomes after surgery in advanced ovarian cancer”. The preliminary analysis in this study showed no association between surgical complexity and global health status at 12 months, whereas extensive surgery did not seem to cause a decrease in patient quality of life compared with preoperative scores 9,24. The currently ongoing international Trial of Radical Upfront Surgical Therapy in advanced ovarian cancer (AGO-OVAR-OP.7/NCT02828618) is set to address more of these important quality-of-life questions25 and also impact of timing of surgery on overall outcome.…”
Section: Discussionmentioning
confidence: 49%
“…8Y10,12 However, even if women seem to adopt active coping strategies, it emerges that a psychopharmacologic therapy in the form of noradrenergic or serotoninergic drugs, with an impact on anguish, is indicated during hospitalization in the 31% of the cases, suggesting that this is a population of long-term cancer survivors characterized by a number of areas of frailty and for whom the specificities of the process of adjustment must be thoroughly investigated. Recently, Soo-Hoo et al 27 reported QoL results, arising from a prospective longitudinal study, in patients who had extensive surgery and standard surgery for ovarian cancer. They found no significant difference in QoL of patients who underwent extensive surgery compared with standard surgery for ovarian cancer, but they did find a falling trend in QoL in the short term (6 weeks to 3 months) after surgery, which gradually returned to baseline at 6 to 9 months after extensive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The SOCQER‐2 study investigated QoL following extensive (high‐SCS or ‘ultra‐radical’) surgery compared with low‐ or intermediate‐SCS surgery in a prospective observational multicentre study design. The a priori hypothesis, based on the pilot study finding, was that QoL in patients undergoing high‐SCS surgery would reduce in the short term postoperatively but would recover to levels comparable with that of patients undergoing less complex surgery by 12 months after surgery 24 . SOCQER‐2 was commissioned by the UK National Institute for Health and Care Excellence (NICE) in order to inform future guidance for ovarian surgery in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…The a priori hypothesis, based on the pilot study finding, was that QoL in patients undergoing high‐SCS surgery would reduce in the short term postoperatively but would recover to levels comparable with that of patients undergoing less complex surgery by 12 months after surgery. 24 SOCQER‐2 was commissioned by the UK National Institute for Health and Care Excellence (NICE) in order to inform future guidance for ovarian surgery in the UK. The study is reported following Strengthening the Reporting of Observational studies in Epidemiology (STROBE) criteria.…”
Section: Introductionmentioning
confidence: 99%